Heresy and Heretics in Deliberatio supra hymnum trium puerorum - Marek Druga (Historický Časopis, 2023)
The study deals with the parts of the work of the Channadic bishop St. Gerard, Deliberatio supra hymnum trium puerorum, in which references to heretics and heresy appear. Gerard mentions the heresy in the broader context of their activities in church history, but he also writes about heretics of his own time, that is, the first half of the 11th century. In this thesis, I analyze Gerard’s accounts of the heretics’ myths, their teachings, and the heretics’ criticisms of the church, church doctrines, and church rites. In the historiography, the heretics of Gerard’s work are often identified with the Bogomils. I therefore compare Gerard’s data on heretics with reports on bogomils from other sources, especially from the works as Sermon against the Bogomils by Cosmas the Priest, the Interrogatio Johannis, and from several Byzantine sources – the letters of Theophylact to the Bulgarian Tsar Peter, the monk Euthymius of the Convent of the Most Venerable Mother of God in Constantinople, and the letter of Euthymius Zigabenus. In the study I devote attention to the question whether Deliberatio proves the presence of Bogomils in Hungary already in the first half of the 11th century. I further address the question of the nature of the so-called pagan uprising, i.e. the social unrest of 1046 in Hungary, the possible participation of bogomils in the uprising, and the testimonial value of Deliberatio also to these important events of Hungarian history in the first half of the 11th century.